2019
DOI: 10.3389/fimmu.2019.00807
|View full text |Cite
|
Sign up to set email alerts
|

From “Serum Sickness” to “Xenosialitis”: Past, Present, and Future Significance of the Non-human Sialic Acid Neu5Gc

Abstract: The description of “serum sickness” more than a century ago in humans transfused with animal sera eventually led to identification of a class of human antibodies directed against glycans terminating in the common mammalian sialic acid N- Glycolylneuraminic acid (Neu5Gc), hereafter called “Neu5Gc-glycans.” The detection of such glycans in malignant and fetal human tissues initially raised the possibility that it was an oncofetal antigen. However, “serum sickness” antibodies were also note… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
98
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 188 publications
(182 reference statements)
0
98
0
Order By: Relevance
“…We have already shown that this novel form of antibodymediated inflammation can potentiate cancer progression in the human-like Cmah-null mouse model (29). Based on these and previous observations we have suggested that xenosialitis may also help explain the increased risk of cancer and CVD epidemiologically associated with human red meat consumption (30).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…We have already shown that this novel form of antibodymediated inflammation can potentiate cancer progression in the human-like Cmah-null mouse model (29). Based on these and previous observations we have suggested that xenosialitis may also help explain the increased risk of cancer and CVD epidemiologically associated with human red meat consumption (30).…”
mentioning
confidence: 67%
“…With regard to the xenosialitis phenom-enon, further work is also necessary to determine the exact pathways by which Neu5Gc is taken up into tissues, and potential approaches to prevent or eliminate such incorporation are being explored. The current findings indicate that this unique example of inflammation driven by a metabolically incorporated dietary glycan (30) is pathologically relevant and may be involved in other inflammation-driven diseases that are known to be associated with red meat consumption, including carcinomas (25), which also appear to be rare in chimpanzees (46). and maintained in the UCSD vivarium according to Institutional Review Board guidelines for the care and use of laboratory animals.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is a nine-carbon negatively charged monosaccharide that can be synthesized by most mammals and found at the tips of carbohydrate chains (glycans), glycoproteins, and glycolipids [ 6 ]. Humans cannot synthesize Neu5Gc due to a deletion in the CMAH gene that encodes the cytidine 5′-monophosphate-Neu5Ac hydroxylase [ 7 ]. Yet, dietary Neu5Gc can be consumed then incorporated at low levels onto human cell surfaces, particularly in cancer, consequently displaying a broad assortment of immunogenic Neu5Gc-glycans [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, dietary Neu5Gc can be consumed then incorporated at low levels onto human cell surfaces, particularly in cancer, consequently displaying a broad assortment of immunogenic Neu5Gc-glycans [ 6 , 8 ]. In fact, all humans examined thus far have a diverse collection of polyclonal anti-Neu5Gc antibodies [ 7 , 9 , 10 ]. Thus, circulating anti-Neu5Gc antibodies continuously encounter Neu5Gc-containing epitopes on human tissues and have been proposed to lead to xenosialitis [ 11 ], which in mice have been shown to exacerbate cancer [ 11 , 12 ] and cardiovascular disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%